The Role of Organizational Learning in Conflict Management - Yıldız, İzlem Gözükara (Business Management and Strategy, 2021)
Conflict is a state of disagreement experienced between two individuals or parties, which can result from many factors. When conflict occurs at organizations, it may lead to many problems such as unaccomplished goals, decreased effectiveness, and low levels of individual and overall performance. However, organizational conflict may positively influence organizations under certain circumstances. The recent literature especially places emphasis on conflict management rather than conflict resolution, as conflicts are likely to enable organizations to enhance their performance and productivity when they are managed in an appropriate way. In this sense, organizations have to develop strategies that are aimed at improving the constructive aspect of conflicts instead of trying to reduce and remove them. As the first step toward this goal, organizations have to provide a learning environment so that they can benefit from conflicts. Since it is considered a key concept for the survival and adaptability of an organization, organizational learning stands out as an effective means of fostering such favorable effects. For this purpose, this article discusses the role of organizational learning in conflict management by examining the factors that facilitate and result from it.